93 Dam parity affects neonatal beef calf energy-related metabolites. (7th December 2018) - Meyer, A; Duncan, N; Foote, A
Abstract: To determine the effects of dam parity on perinatal calf energy metabolism, blood was collected from calves born to primiparous (n = 12; 545.0 ± 49.2 [SD] kg BW; 5.01 ± 0.46 BCS; 276.8 ± 2.3 d gestation length; 7 bull and 5 heifer calves) and multiparous (n = 16; 4.6 ± 3.0 parity; 666.2 ± 64.4 kg BW; 5.28 ± 0.59 BCS; 274.8 ± 2.6 d gestation length; 10 bull and 6 heifer calves) Sim-Angus spring-calving dams bred to single sire. Dams were managed similarly in late gestation, then moved to drylots on gestational d 266 and fed ad libitum tall fescue hay (6.7% CP, 63.9% NDF) with 1.0 kg DM/hd/d DDGS. Calf jugular blood was obtained at 0 (pre-suckling), 6, 12, 24, 48, and 72 h postnatally to determine circulating glucose, insulin, cortisol, NEFA, and triglycerides. Data were analyzed using a mixed model containing effects of parity, hour, and their interaction; hour was a repeated measure. Parity x hour affected ( P ≤ 0.05) all variables except plasma cortisol, which was not affected by parity ( P ≥ 0.18). Serum glucose was greater ( P = 0.03) for calves born to primiparous dams at 0 h, but calves from multiparous dams had greater ( P ≤ 0.04) glucose at 6, 12, 24, and 72 h. Calves from multiparous dams had greater ( P ≤ 0.04) plasma insulin at 12, 48, and 72 h than primiparous. Plasma triglycerides were greater ( P ≤ 0.06) at 6 and 12 h for calves from primiparous dams. Additionally, calves from primiparous dams had greater ( P ≤ 0.02) serum NEFA at 6, 12, and 24 h. In this study, energy-related metabolites were altered in neonatal calves born to heifers. Hormone data suggest this is not a stress-induced response, but rather a difference in perinatal nutrient availability or use.